URGENSI OPTIMALISASI PERAN ADVOKAT DALAM PEMBELAAN PERKARA KORUPSI - Petrus Meirio Mamoh; Dosma Pandapotan (Bajang Institute, 2025)
Advocates hold a strategic position in ensuring the fulfillment of the right to defense for corruption defendants at the Corruption Court. Although this role is regulated in the Advocate Law, the Criminal Procedure Code, and the Corruption Law, in practice advocates often face negative stigma from society that views defense of corruption defendants as supporting corruption itself. In fact, the right to legal defense is part of the principle of due process of law as well as a human right guaranteed by the Constitution. This study aims to examine the urgency of optimizing the role of advocates in defending corruption cases through a normative juridical approach by reviewing relevant laws and legal concepts. The results show that optimizing the role of advocates is essential to overcome various obstacles such as limited access to case files, the implementation of reverse burden of proof, and negative public perception. Optimization can be carried out through harmonization of regulations between the Advocate Law, the Criminal Procedure Code, and the Corruption Law, improving advocates’ competencies in handling corruption cases, and strengthening the protection of defendants’ rights to defense in every stage of the Corruption Court procedural law. Therefore, optimizing the role of advocates is an urgent need to uphold the principle of fair trial in combating corruption in Indonesia.